Integration Issues on User Interface based Web Development - Alpaslan, Gurkan; Kalipsiz, Oya (IEEE, 2017)
User interface prototypes are effective structure for describing as models for web application development thanks to their graphical and dynamic architecture. It provides the benefits such as language independent development, less error-prone and increased quality. The executable programming codes are created by code transformation feature of model-driven development tools as well. Nevertheless, this technique brings the problems along all its benefits. First of all, code transformation from user interfaces by development tools, creates complicated structure to analyze and modify. Another challenge is to deal with the processes which are triggering each other. In addition, data connected process adaptation is a problem as well. All these issues eventually require the integration of discrete modules. This study provides not only a proposal structure to deal with integration problem in web development, but also provides the evaluation criteria for classification of the integration processes.
Keywords: web application development; model-driven development; model integration; Computer Science; Engineering